2017
DOI: 10.1007/s40544-017-0151-0
|View full text |Cite
|
Sign up to set email alerts
|

A technical survey on tire-road friction estimation

Abstract: Lack of driver's knowledge about the abrupt changes in pavement's friction and poor performance of the vehicle's stability, traction, and ABS controllers on the low friction surfaces are the most important factors affecting car crashes. Due to its direct relation to vehicle stability, accurate estimation of tire-road friction is of interest to all vehicle and tire companies. Many studies have been conducted in this field and researchers have used different tools and have proposed different algorithms. This lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(73 citation statements)
references
References 88 publications
0
56
0
Order By: Relevance
“…Most prior works on RFE detection implement experimentbased or model-based approaches to find a correlation between the vehicle dynamics sensor data and road-tire friction related parameters [10]. The recent work in [11] used 6 vehicle sensors as inputs to a neural network (NN) model for prediction of slippery/non-slippery RSC, which controlled the driver maneuvering actions for left or right lane departures.…”
Section: Related Workmentioning
confidence: 99%
“…Most prior works on RFE detection implement experimentbased or model-based approaches to find a correlation between the vehicle dynamics sensor data and road-tire friction related parameters [10]. The recent work in [11] used 6 vehicle sensors as inputs to a neural network (NN) model for prediction of slippery/non-slippery RSC, which controlled the driver maneuvering actions for left or right lane departures.…”
Section: Related Workmentioning
confidence: 99%
“…To study power parameters of interaction of the wheel with seating various methods based on the known analytical models [3][4][5][6] are applied. An important factor when using this or that model is the choice of the suitable law of distribution of specific normal reaction on the length of the contact area of the tire.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, if the lower cutoff angular frequency is taken into account, the actual power spectral density [12] could be expressed as follows:…”
Section: Filtered White Noise Generation For Stochastic Road Surfacementioning
confidence: 99%
“…From all perspectives of research it is found that inadequate skid resistance of pavement is a major cause of traffic accident and the road surface topography is significantly associated with vehicle driving performance [12]. The reconstruction of real and accurate road surface roughness has been discussed both in the fields of automotive engineering and road engineering.…”
Section: Introductionmentioning
confidence: 99%